If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 9whena = 0 Solving 3a + 9aehnw = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '3a'. 3a(1 + 3ehnw) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(1 + 3ehnw)' equal to zero and attempt to solve: Simplifying 1 + 3ehnw = 0 Solving 1 + 3ehnw = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3ehnw = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3ehnw = 0 + -1 3ehnw = 0 + -1 Combine like terms: 0 + -1 = -1 3ehnw = -1 Add '-3ehnw' to each side of the equation. 3ehnw + -3ehnw = -1 + -3ehnw Combine like terms: 3ehnw + -3ehnw = 0 0 = -1 + -3ehnw Simplifying 0 = -1 + -3ehnw The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| 2n+7=10 | | x-0.5+2x-1=0 | | 3y^3(3y+2)= | | 3y^3(3y^2+2)= | | 43x+80y=2000 | | 8z+5i=4+-1z+i | | 4y-10=11 | | h+6=13+2h | | 30p-7=9p+29 | | 5-6x=1+24x | | 20x^4+16x^3+12x^2+2x+3=0 | | 3(z-5)-(2-9z)=-17 | | ln(x^2+x+1)+x+x^4=0 | | 7(8z+2)=8(7z-7) | | ln(x^2+x+1)x+x^4=0 | | 8(a+2)=a+2 | | 4b+9=8b-1 | | 5x+6y=70 | | 13x=(4x+x)2-3x-(4-x)2 | | 13x=(4x+x)*2-3x-(4-x)*2 | | 9a+4=9a+5 | | 2(3*4)+(4+1)= | | 13x=(4+x)*2-3x-(4-x)*2 | | 3x^2-6x+15=-16 | | 8-(3+x)+10x=10*x | | 3y+2=5y+2 | | 2-0.43x=-0.19 | | cotx(cos^2x-4)=0 | | cotx(cosx-4)=0 | | 8b+6=6b | | 4+x=3-4x | | (4y-5x)= |